The correlation between reading habits and their comprehension in senior high school students in Indonesia - Rika Rianti (Concept : Community Concern for English Pedagogy and Teaching, 2025)
This study examines the relationship between reading habits and reading comprehension among senior high school students in Indonesia, employing a systematic literature review method. English, as an international language, plays a vital role in education, where reading becomes an essential skill. This research reviews prior studies that report a range of correlations between reading habits and reading comprehension, with some finding a significant positive relationship and others indicating no correlation. Factors such as vocabulary mastery, motivation, and environment are also identified as variables influencing reading comprehension. The findings of this research are expected to provide policymakers and educators with valuable insights for designing more effective literacy improvement strategies.